E-Module of Meaning in Interpersonal Context in Online Learning: Implementation and Students’ Feedback - Indah Tri Purwanti; Eliwarti Eliwarti; Jismulatif Jismulatif (STAI Hubbulwathan Duri, 2023)
This study aims to develop an e-module of meaning in an interpersonal context for English foreign language (EFL) students studying Semantics. This study was a research and development following the ADDIE model from Branch (2010). The e-module was a pre-lecture consisting of written text, video lectures, videos linked to YouTube, pictures, animated stickers, full of colours and interactive tests. Experts in related fields validated the developed e-module. This study's participants were thefourth-semester undergraduate students majoring in English education at Universitas Riau. The revised version of the e-module was implemented, and the results show that the implementation of the e-module in Semantics learning was effective in improving students’ learning outcomes in Semantics Course. Students’ feedback showed that the e-module is easy to understand, easy to use, attractive, interesting, and easy to remember. The videos in the e-module were perceived to increase their understanding. The participants of this study claimed that their interest, enthusiasm, and motivation in learning increased.